TiO2 Nanotube Layers: Homogeneous Anodic TiO2 Nanotube Layers on Ti–6Al–4V Alloy with Improved Adhesion Strength and Corrosion Resistance (Adv. Mater. Interfaces 12/2019). Issue 12 (21st June 2019) - Hu, Nan; Hu, Tao; Gao, Ang; Gao, Nong; Starink, Marco J.; Chen, Ying; Sun, Wanting; Liao, Qing; Tong, Liping; Xu, Xiaochang; Chu, Paul K.; Wang, Huaiyu
Abstract : Grain‐refinement by employing high pressure torsion can not only eliminate the inhomogeneity of Ti‐6Al‐4V substrate, but also improve the corrosion resistance and adhesion strength of fabricated TiO2 nanotubes. It is thereby a promising strategy to develop metallic biomaterials for bone replacement. Further details can be found in article number1801964 by Liping Tong, Xiaochang Xu, Huaiyu Wang and co‐workers.